Mental health promotion in university students: A systematic review of mental health interventions strategies and implementations - Lamees Mansour (2024)
Background: University students worldwide are increasingly recognised for their vulnerability to mental health conditions, a major public health concern. This systematic review address the critical need for effective mental health interventions tailored to this demographic. By evaluating the reach and implementation strategies of these interventions, the study aims to identify key factors that enhance their effectiveness, thus supporting mental health promotion in university settings. Methods: We are examining primary quantitative studies of various mental health promotion interventions among university students in diverse educational settings globally. Our literature review is based on systematic searches of databases such as PubMed, PsycINFO, Embase, and Scopus from January 2014 to January 2024. Results: Our preliminary searches have identified 598 potential studies, with 96 undergoing detailed eligibility assessments. Of these, 40 have been included for in-depth review. These results are preliminary and provide a foundation for the comprehensive analysis planned. Conclusions: While final conclusions are pending the completion of data analysis, we expect to produce critical insights into effective implementation strategies that enhance the reach and efficacy of mental health promotion interventions. The potential public health actions based on our findings include formulating targeted policies built on proven implementation strategies, enhancing university mental health services through evidence-based practices, and strengthening mental health surveillance systems to continuously monitor and improve student outcomes. Our findings aim to facilitate a tailored approach to mental health interventions to enhance engagement and increase the reach of the promotion interventions while optimising resource use.